IDENTIFICATION OF IMIDAZOLIUM BASED IONIC LIQUIDS DEGRADATION INTERMEDIATES AND DEVELOPMENT OF DEGRADATION PATHWAY - Nooruddin, Aiman (IRC, 2019)
Photocatalytic oxidation (PCO) is one of the most economical and effective treatment among advanced oxidation process to treat organic compound such as ionic liquid that is resistant to biodegradation and is classified as an Advanced Oxidation Process (AOPs). AOPs are typically a chemical treatment procedures designed to remove organic materials in water and wastewater by oxidation through reactions with hydroxyl radicals. The most common type of photocatalyst used for PCO is TiO2.The purpose of this project is to determine the degradation intermediate and pathway of imidazolium-based ionic liquids, and to propose a suitable reaction mechanism via PCO using Fe/TiO2-AC photocatalyst. The methods used to identify the degradation intermediate is by analyzing the intermediates formed by using liquid chromatograph- mass spectrometry LC-MS and nuclear magnetic resonance NMR under specific conditions.